Efeito da radiação gama e do tipo de embalagem sobre as características microbiológicas, físico-químicas e sensoriais de peito de frango refrigerado - Pedro Henrique Salgado Bueno (2008)
Poultry meat is a frequent vehicle for food borne pathogens, which cause danger to its consumers and losses to the meat productive chain. The main objective of this study is to evaluate the effects of gamma irradiation (1.5 and 3.0kGy) in conventional-packed and vacuum-packed broiler breast. The samples were stored under refrigeration (4°C) for 30 days and different microbiological, physic-chemical and sensorial analyses were conducted. Gamma radiation was efficient in both dosages (1.5 and 3.0kGy) in eliminating Salmonella spp., reducing 3 logarithmic cycles of mesophilic aerobic bacteria, total and thermotolerant coliforms. Moulds and yeasts were very resistant to the radiation doses applied. There were no significant changes in meat quality and composition. Lipid oxidation was higher in samples irradiated with 3.0kGy